A MXene-based flexible hydrogel, preparation method and application in pressure sensor
By using the flexible hydrogel prepared by MXENE nano tablets and acrylamide, carboxymethyl cellulose sodium and dopamine combination in the pressure sensor, the problem of the traditional pressure sensor's hard base and conductive polymer dispersion were solved. Conductivity, good elasticity and adhesion performance are suitable for a variety of intelligent perception applications.
Patent Information
- Application Number
- CN202410797689.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-06-20
- Publication Date
- 2025-01-24
- Estimated Expiration
- 2044-06-20
AI Technical Summary
Due to the limitation of the hard substrate, existing pressure sensors are difficult to fit closely with the robot surface, and traditional conductive polymers are unevenly dispersed in the hydrogel, affecting their elasticity and flexibility.
A one-pot polymerization method was used to prepare MXene-based flexible hydrogels. By combining MXene nanosheets with acrylamide, sodium carboxymethylcellulose, and dopamine, a composite hydrogel was formed to improve its conductivity, elasticity, and adhesion properties.
The high -conductivity, good elasticity and adhesion performance of flexible hydrogel are implemented. It is suitable for pressure sensors and can be widely used in the fields of robot touch perception, human -machine interaction, and human motion detection.
Smart Images

Figure CN118725201B_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of pressure sensing, and in particular relates to a MXene-based flexible hydrogel, a preparation method thereof, and an application thereof in a pressure sensor. Background Art
[0002] Electronic skin (e-skin) generally refers to a type of flexible wearable sensor with strong ductility and high flexibility that can simulate human perception and respond to external stimuli. Tough and compressible conductive hydrogels have great development prospects in the fields of flexible sensors, artificial skin and intelligent robots due to their excellent mechanical properties and high conductivity. In recent years, due to the rapid rise of artificial intelligence technology, important branches of the field of artificial intelligence represented by intelligent robots are in urgent need of flexible intelligent bionic sensing sensors. The reason for this phenomenon is that the current traditional pressure sensors are composed of hard substrates, which are very different from the elasticity and flexibility of human skin. In this way, the performance of intelligent robots will be limited in many scenarios. At the same time, flexible wearable strain sensors and flexible pressure sensing devices can solve such problems well with their soft and high elastic characteristics. In recent years, they have received widespread attention in electronic skin, wearable electronic devices, bionic robots, etc. When the device is under pressure, the hydrogel pressure sensor can convert the received pressure signal into a changing resistance signal based on their sensitive characteristics. The principle of the resistive pressure sensor is generally that the sensor is deformed by external pressure, which in turn affects the change of resistance value.
[0003] Hydrogel is a three-dimensional polymer network macromolecular structure with a high water content, which can be cross-linked through covalent bonds, hydrogen bonds and interactions between ions. In recent years, in order to make hydrogels have better mechanical properties, high adhesion properties, long-term stability and high sensitivity, people have developed double-network hydrogels, interpenetrating tough hydrogels, ion-crosslinked tough hydrogels, nano-enhanced hydrogels, and supramolecular interaction tough hydrogels. The performance of hydrogels can be greatly improved by adjusting the structure of the polymer network or doping with different nanomaterials. The conductivity of hydrogels is mainly formed by the conductive materials used to prepare hydrogels. Most of the hydrogel conductive structures are obtained by doping conductive polymers, metal salt solutions and metal nanoparticles. For example, Wang et al. doped Ca into hydrogels. +The addition of metal salt ions to the hydrogel gave it good electrical conductivity and improved the mechanical properties of the hydrogel. Kaur et al. added conductive polymers such as polyaniline, polypyrrole (ppy), and poly (3,4-ethylenedioxythiophene) (PEDOT) as electroactive conductive fillers to the hydrogel to obtain better conductive properties. However, compared with adding MXene nanosheets to the hydrogel, the above scheme may usually have lower conductivity, the conductive polymer may be unevenly dispersed in the hydrogel matrix, and may also affect the elasticity and flexibility of the hydrogel.
[0004] Therefore, how to provide a flexible hydrogel with good elastic properties, high conductivity, and more convenient for use in the manufacture of pressure sensors is a technical problem that needs to be solved urgently by those skilled in the art. Summary of the invention
[0005] In view of this, the present invention discloses a MXene-based flexible hydrogel, a preparation method and its application in a pressure sensor. MXene is superior to certain conductive polymers due to its good biocompatibility, so the MXene-doped hydrogel is applied to pressure sensors due to its good elasticity and high conductivity.
[0006] In order to achieve the above object, the present invention adopts the following technical solution:
[0007] The first technical purpose of the present invention is to provide a MXene-based flexible hydrogel, wherein the MXene-based flexible hydrogel is a PAM / CMC / DA / MXene hydrogel, which is a composite hydrogel prepared by a one-pot polymerization method using acrylamide AM, sodium carboxymethyl cellulose CMC, dopamine DA, and MXene.
[0008] The second technical purpose of the present invention is to provide a method for preparing a MXene-based flexible hydrogel, the method being operated as follows:
[0009] 1) Ti3AlC2 is first selectively etched with hydrochloric acid / lithium fluoride etching solution to obtain MXene nanosheets, and then a dispersed MXene solution is obtained by ultrasound and centrifugation;
[0010] 2) AM, CMC, DA and the MXene solution prepared in step 1) were stirred at a mass ratio of 20:1:1:100 for 1 hour to obtain a stable mixed solution; then, 500 μL of 1% wt N,N'-methylenebisacrylamide (MBAA) as a crosslinker and 300 μL of 10% wt 2,2'-azo[2-(2-imidazoline-2-yl)propane] dihydrochloride (AIBI) as a thermal initiator were added to the mixed solution to initiate free radical polymerization, and the mixture was stirred for 30 minutes and then ultrasonicated to obtain a mixed solution for standby use;
[0011] 3) placing the solution prepared in step 2) in a vacuum environment to remove gas for 3 hours, and quickly pouring the treated solution into a silicone mold; under argon protection, in-situ polymerizing the mixed solution obtained in step 2) in a water bath at 60° C. for 3 hours to obtain PCDM hydrogel, i.e., the MXene-based flexible hydrogel.
[0012] It should be noted that MXene (Ti3C2T x ) is a type of two-dimensional metal carbide with a unique layered structure containing hydroxyl groups on the surface. Therefore, MXene has the metallic conductivity of metal carbides, and it can usually be obtained by etching lithium fluoride with hydrochloric acid. The MXene obtained by etching contains many hydrophilic groups (-OH, -F and =O), which make the two-dimensional metal carbide such as MXene more evenly dispersed in the hydrogel matrix
[30] . In addition, the hydrogel also has good toughness and other mechanical properties. Therefore, it has been widely used in supercapacitors, wearable strain sensors, and friction nanogenerators.
[0013] As the "electronic skin" of robots, hard sensors are obviously not conducive to close fit with the surface of robots. However, the development and progress of science and technology have prompted industry and informatization to enter the flexible era. Flexible sensing technology based on micro-nano new material sensing technology provides a new solution for the tactile perception of intelligent robots. Unlike traditional hard substrate pressure sensing devices, the high flexibility and flexibility of flexible sensors have obvious advantages in the application direction of robots. Flexible pressure sensing devices can also convert pressure signals into electrical signals for robot system recognition. At the same time, thanks to the flexible characteristics of flexible pressure sensing devices, the problem of using traditional hard substrates for intelligent tactile perception of robots is solved. In order to solve the problem that traditional pressure sensors are difficult to attach to robots and other bodies, the adhesion performance of flexible pressure sensor devices is usually improved. Among them, dopamine has good adhesion, reducibility and biocompatibility. Therefore, dopamine and its derived composite materials are widely used in various fields. Dopamine (DA) contains catechol groups, which can increase the adhesion performance of hydrogels on robots and other biological tissues. Adhesion performance is the key performance to improve flexible pressure sensors. By combining dopamine with various nanomaterials, hydrogels will have better adhesion. However, there are still challenges in improving the toughness of traditional flexible pressure sensors, so enhancing the toughness and other mechanical properties of such sensors has become the main task of flexible pressure sensor research. Carboxymethyl cellulose (CMC) is a type of water-soluble anionic biopolymer. It is a non-toxic and odorless white flocculent powder with stable performance and is easily soluble in water. The aqueous solution of carboxymethyl cellulose is a neutral or alkaline transparent viscous liquid. CMC can be used as an adhesive, thickener, etc.
[0014] In the present invention, MXene is added to the composite hydrogel formed by PAM / CMC / DA to form supramolecular interactions, and the catechol group of dopamine significantly enhances the mechanical properties, adhesion properties and electrical properties of the hydrogel. The composite polymer nanohydrogel prepared by the present invention has excellent mechanical and electrical properties, and the flexible pressure sensor made of the hydrogel can be widely used in the fields of detecting human body movement, electronic skin, human-computer interaction and robot tactile perception.
[0015] Further, in step 1), the operation of selectively etching Ti3AlC2 with hydrochloric acid / lithium fluoride etching solution to obtain MXene nanosheets is as follows:
[0016] Ti3AlC2 was added in batches to a precooled LiF / HCl solution and stirred. After the reaction, it was washed and centrifuged until the pH value of the supernatant was stabilized at 6. The resulting precipitate was dispersed in deionized water and sonicated under argon protection. The supernatant was centrifuged, separated and collected to obtain a high-purity MXene nanosheet solution.
[0017] Furthermore, in the LiF / HCl solution, the mass ratio of lithium fluoride to hydrochloric acid is 1:(4.8-5.2); the mass ratio of the LiF / HCl solution to Ti3AlC2 is (5.2-5.5):1, and the temperature of the entire reaction mixture is maintained at 40°C-50°C, and continuous stirring is ensured within this temperature range for 24 hours.
[0018] The third technical objective of the present invention is to provide an application of a MXene-based flexible hydrogel prepared by the method described above in a pressure sensor, wherein the flexible hydrogel can be used to sense the external environment of a robot, to control the robot's movements through pressure-induced electrical signals in a robot system, to achieve intelligent tactile perception of the robot, and can also be used as a hydrogel pressure sensor for human motion detection.
[0019] Compared with the prior art, the present invention has the following beneficial effects:
[0020] The present invention uses a one-pot polymerization method to prepare a composite hydrogel using acrylamide AM, sodium carboxymethyl cellulose CMC, dopamine DA, and MXene, that is, PCDM hydrogel. The composite hydrogel has the advantages of self-adhesion, high sensitivity, large detection range (0-500kPa), low detection limit, high toughness (compression>90%), strong stability (more than 6700s), etc., and can be used for hydrogel flexible pressure strain sensors; wherein,
[0021] Sodium carboxymethyl cellulose (CMC), as a multifunctional thickener and gelling agent, can significantly improve the rheological properties and viscosity in hydrogels, form a cross-linked structure to enhance the mechanical properties, and provide reliable toughness for pressure sensors.
[0022] Dopamine (DA) contains abundant catechol groups, which can adhere to the surface of materials through oxidative polymerization and enhance the bonding strength.
[0023] The hydrogel pressure sensor using the PCDM hydrogel prepared by the present invention for human motion detection can not only accurately track joint movements, sensitively reflect changes in tapping and touching, but also display specific characters such as Morse code; and this technology can be extended to robot systems to control robot movements through pressure-induced electrical signals. Therefore, the present invention has a very promising application prospect in the field of human-computer interaction and human motion signal detection.
[0024] In summary, PAM / CMC / DA / MXene hydrogel pressure sensors have excellent mechanical properties, electrical properties, adhesion properties, etc., providing a more reliable solution for flexible wearable electronic skin, human-computer interaction, tactile perception and other fields. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on the provided drawings without paying creative work.
[0026] Figure 1 (a) Schematic diagram of the process of preparing PCDM hydrogel; (b) Schematic diagram of the internal structure of the hydrogel network and the molecular interactions of the hydrogel network.
[0027] Figure 2 (a) Schematic diagram of the tensile testing machine; (b) XRD patterns of Ti3AlC2 and MXene; (c) SEM image of PCDM hydrogel at 50 μm; (d) SEM image of PCDM hydrogel at 100 μm.
[0028] Figure 3 (a) Compressive stress-strain curves of PAM / CMC / DA hydrogels at different ratios of AM to CMC; (b) Compressed stress-strain curves of PAM / CMC / DA hydrogels at a ratio of AM to CMC of 20:1 after 50%-90% compression; (c) Figure 3 (b) The corresponding maximum stress and energy dissipation diagram; (d) The compressive stress-strain curves of PAM / CMC / DA hydrogels at different ratios of AM to DA; (e) The compressive stress-strain curves of PAM / CMC / DA hydrogels at a ratio of AM to DA of 20:1 after 50%-90% compression; (f) Figure 3(e) Corresponding maximum stress and energy dissipation diagram; (g) Tensile stress-strain curves of PAM / CMC / DA hydrogels at different ratios of AM to CMC; (h) Compressive stress-strain curves of PAM / CMC / DA hydrogels without MXene when the ratio of AM to CMC and the ratio of AM to DA are both 20:1 at the maximum strain of 50% during loading / unloading; (i) Compressive stress-strain curves of PAM / CMC / DA / MXene hydrogels with MXene when the ratio of AM to CMC and the ratio of AM to DA are both 20:1 at the maximum strain of 50% during loading / unloading.
[0029] Figure 4 (a) Relative resistance and strain change curves of PCDM hydrogel pressure sensor; (b) relative resistance change of PAM / CMC / DA / MXene hydrogel pressure sensor under small strain and (c) large strain; (d) response time and recovery time of sensor under 60% strain; (e) compression-release response curve of PCDM pressure sensor in the strain range of 0-60%; (f) comparison of response curves of hydrogel pressure sensor under different compression rates; (g) long-term stability curve of PAM / CMC / DA / MXene hydrogel pressure sensor under 50% strain response; (h) schematic diagram of the effect of compression of hydrogel pressure sensor on the brightness change of LED light.
[0030] Figure 5 (a) Photographs of PCDM hydrogels adhering to objects of different materials and weights; (b) Schematic diagram of shear force experiment; (c) Adhesion strength curves of PCDM hydrogels with different ratios of acrylamide (AM) to dopamine (DA) on glass plate; (d) Adhesion strength curves of PCDM hydrogels with different ratios of acrylamide (AM) to dopamine (DA) on wooden board; (e) Adhesion strength curves of PCDM hydrogels with different ratios of acrylamide (AM) to dopamine (DA) on pig skin; (f) Adhesion energy diagram for three materials and three ratios; (g) Adhesion performance diagram of PCDM hydrogels with a ratio of 10:1 to acrylamide (AM) to dopamine (DA) on three substrates after three consecutive tests.
[0031] Figure 6The following are the experimental results of the adhesion strength of three different ratios of PCDM hydrogel acrylamide (AM) and dopamine (DA) on three substrates in three consecutive tests. (a) The ratio of acrylamide to dopamine was 10:1 and tested on a glass plate for three consecutive times; (b) The ratio of acrylamide to dopamine was 20:1 and tested on a glass plate for three consecutive times; (c) The ratio of acrylamide to dopamine was 30:1 and tested on a glass plate for three consecutive times; (d) The ratio of acrylamide to dopamine was 10:1 and tested on a wooden board for three consecutive times; (e) The ratio of acrylamide to dopamine was 20:1 and tested on a wooden board for three consecutive times; (f) The ratio of acrylamide to dopamine was 30:1 and tested on a wooden board for three consecutive times; (g) The ratio of acrylamide to dopamine was 10:1 and tested on pig skin for three consecutive times; (h) The ratio of acrylamide to dopamine was 20:1 and tested on pig skin for three consecutive times; (i) The ratio of acrylamide to dopamine was 30:1 and tested on pig skin for three consecutive times.
[0032] Figure 7 (a) "UPC" Morse code curve generated by PCDM hydrogel pressure sensor; (b) "MXene" Morse code curve generated by PCDM hydrogel pressure sensor; (c) response curve when tapping the PCDM hydrogel pressure sensor with a finger; (d) response curve when touching the PCDM hydrogel pressure sensor with a finger.
[0033] Figure 8 (a) Schematic diagram of fixing the PCDM hydrogel pressure sensor on the human body; (b) Response curve of the PCDM hydrogel sensor at different wrist bending degrees; (c) Response curve of the PCDM hydrogel sensor at different elbow bending degrees; (d) Response curve of the PCDM hydrogel sensor at different knee bending degrees.
[0034] Fig. 9 (a) Bluetooth data acquisition control circuit composed of PCDM hydrogel pressure sensor, single-chip microcomputer and peripheral circuit; (b) Installation location of PCDM hydrogel pressure sensor; (c) Installation location of multi-channel data acquisition equipment; (d) When the robot body is touched, the robot moves back to avoid; (e) When the robot's left hand is touched, the robot raises its left arm to elbow; (f) When the robot's left leg is touched, the robot squats in a alert posture. DETAILED DESCRIPTION
[0035] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0036] The word "embodiment" used here as an "exemplary" does not necessarily mean that any embodiment described is superior to or better than other embodiments. Unless otherwise specified, the performance index tests in the embodiments of this application are performed using conventional test methods in the art. It should be understood that the terms described in this application are only used to describe specific implementation methods and are not used to limit the content disclosed in this application.
[0037] Unless otherwise specified, the technical and scientific terms used in this document have the same meanings as commonly understood by ordinary technicians in the technical field to which this application belongs; other experimental methods and technical means not specifically specified in this application refer to experimental methods and technical means commonly used by ordinary technicians in this field.
[0038] In the description of the present invention, it is necessary to understand that the terms "middle", "upper", "lower", "ascending", "descending", "vertical", "face", "top", "bottom", "inside", "outside", etc., indicating the orientation or position relationship are based on the orientation or position relationship shown in the drawings, and are only for the convenience of describing the present invention and simplifying the description, rather than indicating or implying that the referred device or element must have a specific orientation, be constructed and operated in a specific orientation, and therefore cannot be understood as a limitation on the present invention.
[0039] In order to better illustrate the content of the present application, numerous specific details are provided in the specific examples below. It should be understood by those skilled in the art that the present application can also be implemented without certain specific details. In the embodiments, some methods, means, instruments, equipment, etc. well known to those skilled in the art are not described in detail in order to highlight the main purpose of the present application.
[0040] Under the premise of no conflict, the technical features disclosed in the embodiments of the present application can be combined arbitrarily, and the resulting technical solutions belong to the contents disclosed in the embodiments of the present application.
[0041] The invention discloses a MXene-based flexible hydrogel, a preparation method and application in a pressure sensor.
[0042] Example 1
[0043] A method for preparing a MXene-based flexible hydrogel (PAM / CMC / DA / MXene hydrogel) is as follows:
[0044] 1) Materials
[0045] Titanium aluminum carbide powder (Ti3AlC2), lithium fluoride (LiF), dopamine hydrochloride (DA), carboxymethyl cellulose (CMC), acrylamide (AM), 2,2′-azo[2-(2-imidazolin-2-yl)propane] dihydrochloride (AIBI), and N,N′-methylenebis(acrylamide) (MBAA) were purchased from Shanghai MacLean Biochemical Co., Ltd. (Shanghai, China). Concentrated hydrochloric acid was purchased from Sinopharm Chemical Reagent Co., Ltd. (Shanghai, China). All reagents were processed with high purity and no further purification was required. All solutions were dissolved in deionized water.
[0046] 2)MXene(Ti3C2T x )
[0047] Ti3AlC2 was chemically etched using LiF / HCl solution to synthesize structurally uniform MXene nanosheets. The detailed preparation process is as follows:
[0048] In the initial stage, 2 grams of LiF were mixed with 20 mL of 9M hydrochloric acid and stirred for 5 minutes under magnetic stirring to ensure adequate mixing. In order to accurately control the temperature of the reaction system and avoid excessive temperature due to exothermic reaction, the etching solution was cooled in a water bath containing ice cubes. Then, 2 grams of Ti3AlC2 were added to the pre-cooled mixed solution in small batches, and the temperature of the overall reaction mixture was maintained at 35°C. This measure was to alleviate the drastic temperature fluctuations that may be caused by the exothermic reaction. In addition, continuous stirring was ensured for 24 hours in the temperature range of 40 to 50°C, while maintaining proper ventilation of the container to exhaust possible gases. After the reaction was completed, the reaction mixture was washed several times with deionized water and centrifuged at 3500 rpm for 5 minutes. This step was repeated until the pH value of the supernatant stabilized at 6. Thereafter, the resulting precipitate was collected and redispersed in deionized water, and ultrasonic treatment was performed for 1 hour under argon protection, while an ice water bath was used to prevent possible heat accumulation during the ultrasonic process from causing irreversible damage to the sample. The last step was to separate and collect the supernatant by centrifugation at 3500 rpm for 1 h to obtain the desired high-purity MXene nanosheet solution.
[0049] 3) Preparation of PAM / CMC / DA / MXene hydrogel
[0050] 0.1g CMC was added to the MXene aqueous solution prepared by the above method, and it was stirred continuously for 2h to fully dissolve it. MXene is the main component of the hydrogel, and its concentration may affect the structure, mechanical properties and chemical properties of the hydrogel. Then, 0.1g DA was added to the above solution and stirred for 0.5h, and then 2g AM was added to the mixed solution and stirred evenly. The amount of CMC and DA added during the preparation process may affect the viscosity, adhesion and mechanical properties of the hydrogel. Then, 500μL of 1%wt N,N′-methylenebisacrylamide (MBAA) was added to the mixed solution as a crosslinker, and 300μL of 10%wt 2,2′-azo[2-(2-imidazoline-2-yl)propane] dihydrochloride (AIBI) was added as a thermal initiator to initiate free radical polymerization. AM is a crosslinker, and its addition amount may affect the crosslinking density and network structure of the hydrogel, thereby affecting its mechanical properties and stability. In order to avoid the influence of bubbles in the prepared hydrogel on its performance, the prepared solution was placed in a vacuum environment to remove gas for 3 hours, and the treated solution was quickly poured into a silicone mold. In the final stage of the preparation process, the hydrogel was in situ polymerized at 60 ° C for 3 hours under argon protection to obtain PCDM hydrogel. The exhaust process is crucial for the removal of bubbles in the hydrogel and may affect the density and microstructure of the hydrogel. In situ polymerization conditions include factors such as temperature, time and atmosphere, which may affect the cross-linking degree, pore structure and chemical stability of the hydrogel. During the preparation of the hydrogel, by adjusting the addition ratio of carboxymethyl cellulose (CMC) and dopamine (DA), composite structure hydrogels with different CMC and DA concentrations can be successfully prepared. This method allows precise control of the chemical composition in the hydrogel, thereby achieving directional adjustment of its properties.
[0051] 4) Characterization and measurement
[0052] X-ray diffractometer (XRD, Rigaku D / Max 2500PC) was used to analyze the phase of the prepared materials to explore their structural characteristics.
[0053] The surface morphology and microstructure of the hydrogel samples were characterized by scanning electron microscopy (SEM, Hitachi S-4800, Japan). Before SEM characterization of the hydrogel samples, the hydrogel samples were brittlely broken with liquid nitrogen and then freeze-dried in a -80℃ freeze dryer for 96h.
[0054] The mechanical properties of the hydrogel, the adhesion properties and other performance tests were all measured using a tensile testing machine (TM2101-T5). In addition, a digital multimeter (Keysight 34470A) from Agilent Technologies was used to perform a sensing test on the hydrogel pressure sensor and the results were displayed on the host computer.
[0055] Example 2
[0056] The preparation method of a MXene-based flexible hydrogel (PAM / CMC / DA / MXene hydrogel) is the same as that in Example 1 above, except that 0.2 g CMC and 0.2 g DA are added, and the remaining steps are the same.
[0057] Example 3
[0058] The preparation method of a MXene-based flexible hydrogel (PAM / CMC / DA / MXene hydrogel) is the same as that in Example 1 above, except that 0.08 g CMC and 0.05 g DA are added, and the remaining steps are the same.
[0059] 1. Preparation and mechanism of PAM / CMC / DA / MXene hydrogel
[0060] In order to integrate MXene nanosheets with excellent electrical conductivity into the composite hydrogel composed of PAM, CMC and DA, a one-pot method was used to synthesize PAM / CMC / DA / MXene hydrogel. Figure 1 a shows the flow chart of hydrogel preparation, cross-linking between monomers to form long chains and intermolecular interactions to form the composite structure in the hydrogel.
[0061] First, MXene nanosheets were obtained by selectively etching Ti3AlC2 with hydrochloric acid / lithium fluoride etching solution, and then a dispersed MXene solution was obtained after ultrasonic and centrifugation. Then, AM, CMC, DA and MXene solution were fully stirred for 1 hour to obtain a stable mixed solution. Subsequently, 500 μL of 1% wt N, N'-methylenebisacrylamide (MBAA) was added to the mixed solution as a crosslinker, and 300 μL of 10% wt 2,2'-azo[2-(2-imidazoline-2-yl)propane] dihydrochloric acid (AIBI) was used as a thermal initiator to initiate free radical polymerization. Stir for 30 minutes to allow the solution to be evenly distributed. After ultrasonication for 10 minutes, it was placed in a silicone mold. After that, under argon protection, the PCDM hydrogel was obtained after polymerization in a water bath at 60°C for 3 hours. During the preparation process, different amounts of CMC and DA were added to fix the amount of AM. The mass ratios of AM to CMC are 10:1, 15:1, 20:1, 30:1, and the mass ratios of AM to DA are 10:1, 20:1, 40:1, 100:1, respectively. Composite hydrogels with different concentrations of CMC and DA can be prepared. The composite structure of the hydrogel includes a variety of suspended chains and ring defects. Figure 1 As shown in Figure b, the following interactions are most likely to occur between acrylamide, sodium carboxymethyl cellulose, dopamine and MXene. When sodium carboxymethyl cellulose is added to the hydrogel, strong hydrogen bonds can be formed between sodium carboxymethyl cellulose and the polar groups in the long polymer PAM chain. The carboxyl and hydroxyl groups in sodium carboxymethyl cellulose can form hydrogen bonds with the amino and hydroxyl groups in the dopamine molecule. The stacking of π-π bonds is most likely to occur between the oxidation products of dopamine and MXene or other organic molecules containing conjugated π electron systems. In addition, the rich functional groups (such as -O, -F, -OH, etc.) on the surface of MXene nanosheets can provide a large number of hydrogen bonding sites for non-covalent hydrogen bonding interactions with PAM. Therefore, the hydrogel network composed of acrylamide, sodium carboxymethyl cellulose, dopamine and MXene interacts in various ways to form a network structure rich in hydrogen bonds. The interactions between these different modes can enhance the composite structure of the hydrogel, thereby greatly improving the compressibility and toughness of the hydrogel.
[0062] 2. Measurement Instruments and Characterization Results
[0063] like Figure 2 As shown in a, this is a schematic diagram of the test device. A tensile testing machine (TM2101-T5) is used to test the mechanical properties and adhesion properties of the hydrogel. In addition, a digital multimeter (Keysight34470A) from Agilent Technologies is used to perform a sensing test on the hydrogel pressure sensor, which is displayed on the host computer. Figure 2As shown in b, this is the XRD spectrum of Ti3AlC2 and MXene, which can prove that the prepared MXene nanosheets are successful because its XRD spectrum has an obvious characteristic peak (002) at 6.6°. Figure 2 As shown in c and d, the scanning electron microscope (SEM) characterization of the prepared PCDM composite network structure hydrogel at 50μm and 100μm proves that the PCDM hydrogel has an excellent three-dimensional pore structure, which lays the foundation for its good mechanical properties.
[0064] 3. Mechanical properties of PCDM hydrogel pressure sensor
[0065] Since flexible pressure sensors require good mechanical stability, good recoverability, and superior toughness to maintain a long application life, the mechanical properties of PCDM hydrogels were explored through a series of loading-unloading cycle tests on a tensile machine. Since sodium carboxymethyl cellulose, dopamine and other ingredients were added to the hydrogel, the synthesized hydrogel obtained excellent mechanical properties. Compared with the mechanical property defects of single network hydrogels, composite structure network hydrogels have obvious advantages, which is because composite structure network hydrogels can be composed of different brittle and tough networks. Due to the existence of an interpenetrating network structure, under conditions of appropriate moisture content, the more brittle polyacrylamide (PAM) network is responsible for energy dissipation during the deformation of the hydrogel, resulting in an increase in the elastic modulus. However, although this brittle network enhances the structural rigidity of the hydrogel, it also sacrifices the ductility of the composite hydrogel.
[0066] In order to explore the optimal compression performance and toughness of PAM / CMC / DA hydrogel (without MXene), the mass of PAM was fixed at 2g, and the ratio of PAM to CMC and the ratio of PAM to DA were continuously adjusted. The mass ratios of AM to CMC were 10:1, 15:1, 20:1, and 30:1, and the mass ratios of AM to DA were 10:1, 20:1, 40:1, and 100:1, respectively. Figure 3 As shown in a, when the ratio of AM to DA is fixed at 40:1, the mass ratios of AM to CMC are 10:1, 15:1, 20:1, and 30:1, respectively, and the compression is 90% without breaking. When the ratio of AM to CMC is 20:1, the compression performance reaches the maximum, and the stress can reach 160kPa. Figure 3 As shown in b, when the ratio of AM to CMC was 20:1, the hydrogel was tested under different compressive stresses of 50%-90%, and it was found that the maximum stress and energy dissipation of the hydrogel increased significantly. Figure 3As shown in Figure c, this indicates that the hydrogel has good resistance to external strain. The strain of different ratios of AM and CMC was tested when the ratio of AM to DA was fixed at 40:1. Now, the strain of different mass ratios of AM and DA was tested when the optimal mass ratio of AM to CMC was fixed at 20:1. Figure 3 As shown in Figure d, different ratios of AM to DA were tested, 10:1, 20:1, 40:1, and 100:1. It was found that the compression performance reached the maximum when the mass ratio of AM to DA was 20:1, and the stress was significantly increased to 500 kPa. Figure 3 As shown in Figure 5, when the ratio of AM to DA was 20:1, the hydrogel was tested for different compression stresses of 50%-90%, and it was found that the maximum stress and energy dissipation of the hydrogel increased significantly. Figure 3 As shown in f, the maximum energy dissipation can reach 1500kJ / m 3 This shows that the hydrogel with this drug ratio has better resistance to external strain and toughness. In addition, in order to explore whether the addition of CMC will improve the tensile properties of the hydrogel, a tensile test was conducted at different ratios of AM and CMC. Figure 3 As shown in g, when the ratio of AM to CMC is 20:1, the elongation at break can reach 1000% and the stress is 190 kPa, which is consistent with Figure 3 The situations shown in a confirm each other. The toughness and fatigue resistance of the hydrogel were studied through compression and tension tests.
[0067] Next, in order to explore the effect of the addition of MXene on the mechanical properties of the hydrogel, a hydrogel loading / unloading test was performed for 30 consecutive cycles under 50% compressive strain. Figure 3 h and Figure 3 As shown in Figure i, most of the hysteresis curves of the tests overlap. In addition, it may be due to the initial loosening and large energy dissipation of the internal network of the hydrogel, resulting in a more obvious stress hysteresis curve in the first cycle. The first compression cannot immediately restore the good mechanical properties of the PCDM hydrogel, but in the subsequent dozens of loading / unloading compression experiments, the hysteresis curves basically overlap, which shows that the PCDM hydrogel has a certain degree of mechanical performance reliability. For example Figure 3 h and Figure 3 It can be seen that the addition of MXene nanosheets further increases the toughness and mechanical properties of the hydrogel, and the high compressive strength is still maintained after recovery. This rapid self-recovery is attributed to the dissociation and combination of dynamic borate and π-π stacking bonds in the hydrogel network. Therefore, it can be concluded that PCDM hydrogel can have excellent fatigue resistance and mechanical properties within the 90% stress range, which is conducive to further exploring the strain sensitivity of the hydrogel.
[0068] 4. Electrical properties of PCDM hydrogel pressure sensor
[0069] MXene nanosheets are a class of excellent nanomaterials composed of transition metal carbides, generally transition metal carbides and fluorine (X) composed of surface groups. The transition metal carbide layers are stacked alternately by fluoride ions to form a layered structure of MXene nanosheets. As an excellent conductive filler, it has abundant surface active sites and can form a conductive network, greatly improving the conductive properties of the hydrogel. Sensitivity is the primary parameter of the hydrogel pressure sensor. The sensitivity of the pressure sensor is usually defined as the gauge factor (GF). The calculation formula of the gauge factor (GF) is defined as GF = (ΔR / R0) / ε, where ε is the strain of the hydrogel sensor.
[0070] like Figure 4 As shown in a, the resistance value of the hydrogel pressure sensor decreases with continuous pressing. In order to unify the standard, the change in resistance is defined as a positive value, so the sensitivity increases with the increase in strain. The results show that the range of response and strain is not linear. After GF curve fitting, the sensitivity is 0.4 when pressing 0%-60%, the sensitivity is 2.61 when pressing 60%-80%, and the sensitivity is 1.04 when pressing 80%-90%. Figure 4 As shown in b and c, the sensor is tested for loading and unloading cycles under compression of 10%-60% strain. The PCDM strain sensor remains stable in five cycles of pressure 0-27kPa (10%-60% strain), proving its excellent stability and repeatability. This is because the surface of MXene nanosheets has a large number of active sites, and its introduction can establish a large number of hydrogen bonds, which can quickly conduct electrons and interact with molecules in the hydrogel, so it also has a very fast response speed to small strains.
[0071] In addition, if Figure 4 As shown in Figure d, the PCDM hydrogel has a relatively fast response to compression and recovery. When the hydrogel pressure sensor is compressed from the initial state to 60% (pressure is 27 kPa), its compression response time is 160 ms, and its recovery response time is 180 ms. Figure 4 As shown in Figure e, when the strain sensor is compressed to 30% (pressure 5.5 kPa), 40% (pressure 10 kPa), 50% (pressure 15 kPa) and 60% (pressure 27 kPa) and maintained for a period of time, the relative resistance change of the sensor is also gradually increasing, and it has good stability and the same response time during the compression and release process. Figure 4 As shown in Figure 5, the sensor has the same response at different compression rates, proving that the compression rate has no effect on the magnitude of the response. In addition, the response time is positively correlated with the compression rate. Figure 4 As shown in Figure g, the relative change of the resistance of the pressure sensor after 6700s of 40% compression cycle has no obvious change, and the figure shows three amplified curves, among which the shapes of the ten response curves are almost the same. Therefore, it can be considered that the sensor still has excellent long-term repeatability and stability in long-term loading-unloading tests. Figure 4 As shown in Figure h, the pressure sensor and LED are connected in series to form a loop, and are stimulated by an external 5V power supply. In the original state, the LED light is dim. After pressing the pressure sensor, its resistance value decreases, and the current in the loop increases, so the LED light becomes brighter.
[0072] 5. Adhesion properties of PCDM hydrogel pressure sensor
[0073] In addition to the excellent mechanical and electrical properties mentioned above, PCDM hydrogel also has good adhesion properties. This is due to the fact that dopamine (DA) contains multiple catechol groups (-OH), which have strong hydrophilicity and activity. The catechol groups can form chemical bonds or hydrogen bonds with other compounds containing active groups, thereby promoting the formation of a composite structure network of PCDM hydrogel and greatly enhancing the adhesion properties of the hydrogel. Adhesion experiments were conducted on PCDM hydrogel, such as Figure 5 As shown in Figure a, PCDM hydrogel can adhere to the surfaces of many objects of various shapes and materials, such as metal, glass, plastic and other materials. In addition, due to the adhesion of hydrogel, it can also adhere to different weights of different materials by adhering hydrogel to rubber gloves. For example, the tested objects include 35g metal weights, 62g glass beakers, and 95g plastic weights.
[0074] In order to have a quantitative index for the adhesion performance of the hydrogel, the present invention conducted a shear force experiment. Figure 5 As shown in Figure b, the hydrogel is sandwiched between substrates, including a clean glass plate, a wood board treated with a UV light cleaner, and fresh pig skin. Figure 5 As shown in c, d, and e, the adhesion of PCDM hydrogels with different ratios of acrylamide (AM) and dopamine (DA) of 10:1, 20:1, and 30:1 was tested. Figure 5 c is the test on the glass plate, Figure 5 d is the test of the wooden board, Figure 5 e is the test on pig skin. Observation Figure 5c, d, and e can draw a unified conclusion. Among the different ratios of acrylamide (AM) and dopamine (DA), under the same mass of acrylamide (AM), the PCDM hydrogel with the highest dopamine (DA) content has stronger adhesion strength, that is, when the mass ratio of AM to DA is 10:1, the adhesion strength is stronger than that of the mass ratio of 20:1 and 30:1. The second highest adhesion strength is when the ratio of acrylamide (AM) to dopamine (DA) is 20:1, and the lowest adhesion strength is when the ratio of acrylamide (AM) to dopamine (DA) is 30:1. After treating the wooden board with UV light cleaning agent, the fine impurities on its surface were cleaned off and the roughness of the wooden board surface was increased, so it has a higher adhesion strength in the test. In addition, it has been proved that the higher the dopamine content, the more catechol groups it has. The catechol groups in dopamine have excellent hydrophilicity and activity, and can form chemical reactions such as hydrogen bonds with other active groups, which can improve the adhesion properties of PCDM hydrogel. Figure 5 f), which expresses the adhesion energy dissipation used in the three materials and three ratios, that is, the work done to overcome the adhesion force. For example, when the ratio of acrylamide (AM) to dopamine (DA) is 10:1, the adhesion energy dissipation used by the glass plate is 746.89 J / m 2 , the adhesion energy dissipation used by the wood board is 1997.81J / m 2 The adhesion energy dissipation of pigskin is 2312.51 J / m 2 However, the strongest adhesion to pig skin can be generally explained by the fact that the interwoven microfibers formed by CMC and DA in the PAM hydrogel help to increase the contact area and contact strength between the hydrogel and the pig skin surface, thereby improving adhesion. Figure 5 As shown in Figure g, it shows that after three consecutive adhesion performance experiments on three substrates using PCDM hydrogels with a ratio of acrylamide (AM) to dopamine (DA) of 10:1, the adhesion energy dissipation decreased slightly. However, the PCDM hydrogel still has good repeatable and lasting adhesion. This is because the strong adhesion between the PCDM hydrogel and different substrates is due to the interaction of the surface functional groups of both parties. For example, van der Waals forces, electrostatic interactions and hydrogen bonds. Among them, the catechol group in dopamine (DA) has generated an indispensable force for the improvement of adhesion performance, providing favorable conditions for the self-adhesion of PCDM hydrogels on robots and other human-machine interaction devices.
[0075] Figure 6The experimental results of the adhesion strength of three different ratios of PCDM hydrogel acrylamide (AM) and dopamine (DA) on three substrates for three consecutive experiments. It can be seen from the figure that the adhesion strength will gradually weaken after three cycles, but it still has a high adhesion strength. (a) The ratio of acrylamide to dopamine is 10:1 and tested on a glass plate for three consecutive times. (b) The ratio of acrylamide to dopamine is 20:1 and tested on a glass plate for three consecutive times. (c) The ratio of acrylamide to dopamine is 30:1 and tested on a glass plate for three consecutive times. (d) The ratio of acrylamide to dopamine is 10:1 and tested on a wooden board for three consecutive times. (e) The ratio of acrylamide to dopamine is 20:1 and tested on a wooden board for three consecutive times. (f) The ratio of acrylamide to dopamine is 30:1 and tested on a wooden board for three consecutive times. (g) The ratio of acrylamide to dopamine is 10:1 and tested on pig skin for three consecutive times. (h) The ratio of acrylamide to dopamine is 20:1 and tested on pig skin for three consecutive times. (i) The ratio of acrylamide to dopamine was 30:1 and tested three times on pig skin.
[0076] 6. Application design of PCDM hydrogel pressure sensor
[0077] Because PCDM hydrogels have excellent conductivity, good skin adhesion, excellent compression performance, and high strain response, they provide favorable conditions for use as flexible wearable sensors. When they are fixed on an object that needs to sense external contact or pressure, pressure information can be transmitted. In order to more intuitively demonstrate the effect of the sensor in practical applications. The sensor was fixed on the desktop and connected to the data acquisition system experimental instrument with copper wire. The resistance change of the sensor was then collected. The difference between tapping and touching in the sensor is similar to the point (short press or tap) and line (long press or touch) in Morse code.
[0078] like Figure 7 As shown in a and b, the above characteristics are used to realize the transmission of simulated telegraph, showing the Morse code information of China University of Petroleum (East China) (UPC) and MXene generated by tapping the sensor respectively. Figure 7 As shown in Figure c, when the sensor is tapped lightly with a finger, a response peak will appear in the sensor, and the magnitude of the response will increase as the tapping force increases. Figure 7 As shown in Figure d, when the sensor is pressed with a finger, it will produce a response and maintain for a short period of time until it is not touched, and then the response disappears. In summary, the application tests show that the PCDM hydrogel pressure sensor has the ability to sense contact signals.
[0079] PCDM hydrogel pressure sensor can sense the pressure signal of the object being measured. When the PCDM hydrogel pressure sensor is placed on various joints of the human body, the physiological signal of the human body becomes the information to be measured, so the sensor can detect the physiological information of the human body. Figure 8 As shown in a, in order to evaluate the potential of the sensor in practical applications, its sensing characteristics at various joints of the human body were experimentally tested. Figure 8 As shown in b, the signal response of the pressure sensor installed on the human wrist is shown. The response of the sensor is observed by continuously bending the wrist at different angles. When the wrist is not bent, the response of the sensor is 0. When the wrist is bent 30°, it produces about 25% response. When the wrist continues to bend 60°, the response continues to increase to 45%. When the wrist is finally fully bent to 90°, the response also increases to about 70%. Similarly, the PCDM hydrogel pressure sensor is fixed to other joints of the human body. Figure 8 As shown in Figure c, the hydrogel sensor was tested for continuous bending at 30, 60, and 90 degrees at the elbow, and returned to its original position after being held at each angle for a certain period of time. This process was repeated twice. It can be observed that the response size increases with the degree of bending, and the response remains almost unchanged during this period of time. In addition, the sensor was placed at the knee, and the repeatable response of the knee joint bending 90° could be detected ( Figure 8 d). This proves that the application of PCDM hydrogel pressure sensor in monitoring human physiological signals has great application prospects.
[0080] 7. Application of hydrogel pressure sensor in robot intelligent tactile perception
[0081] In order to verify the application of this sensor in robot intelligent tactile perception, the PCDM hydrogel pressure sensor is combined with the robot system. PCDM hydrogel pressure sensor can be used as the robot's bionic electronic skin to provide the robot with tactile signal perception. Its working idea is as follows Fig. 9 As shown in a. The PCDM hydrogel pressure sensor is placed in a voltage divider circuit, in which the reference voltage is 3.3V. The electrical signal is amplified through an amplifier. The voltage is then collected through the analog-to-digital converter in the MCU. The analog-to-digital converter is a module that converts analog signals into digital signals. After the data information is collected, the MCU transmits it to the Bluetooth module on the robot side through a Bluetooth module such as HC-05, so as to realize real-time data collection and information communication, and then realize real-time control feedback of the robot. Therefore, the PCDM hydrogel pressure sensors are placed in various parts of the humanoid robot's body, such as the torso, back of the hand, thigh, etc. Fig. 9 As shown in b and c.
[0082] Since PCDM hydrogel has good adhesion, in order to prevent the hydrogel from adhering to rubber gloves, polyimide tape (PI tape) was attached to the surface of the hydrogel pressure sensor. Fig. 9 As shown in d, e, and f, when the pressure sensor of a certain part of the robot is pressed, the PCDM hydrogel pressure sensor at that part will produce a change in the resistance signal. The data acquisition system will collect and process this electrical signal and transmit it to the robot end to determine the part of the robot that is pressed and drive that part to perform the corresponding action. Fig. 9 As shown in d, by pressing the hydrogel pressure sensor on the trunk, the robot will take a step back to avoid contact. Fig. 9 As shown in e, by pressing the hydrogel pressure sensor on the left hand, the robot can defend itself and swing its left fist to drive away. Fig. 9 As shown in Figure f, by pressing the hydrogel pressure sensor on the left thigh, the robot can change to a half-squat state to be alert. This proves that the application of PCDM hydrogel pressure sensor in human-computer interaction has great application prospects.
[0083] In summary, the present invention uses MXene suspension and one-pot polymerization method to prepare a hydrogel flexible pressure sensor with self-adhesion, high sensitivity, large detection range (0-500kPa), low detection limit, high toughness (compression>90%), and strong stability (over 6700s). It has very promising application prospects in the field of human-computer interaction and human motion signal detection. This article can demonstrate that sodium carboxymethyl cellulose (CMC) is a multifunctional thickener and gelling agent. The higher the content of sodium carboxymethyl cellulose added, the more the toughness of the hydrogel is improved, and the mechanical properties of the hydrogel can be enhanced.
[0084] In addition, this article can also verify that the higher the content of dopamine (DA) added, the more the adhesion performance of the hydrogel is improved, and the mechanical properties of the hydrogel can be enhanced. The pressure strain sensor is applied to human motion detection, and the flexion and extension of each joint can be accurately detected. In addition, tapping and touching the pressure sensor can sensitively display changes in tactile sensation, thereby displaying specific characters by tapping Morse code. The pressure sensor is then combined with a robotic system. An electrical signal is generated by pressing the hydrogel pressure sensor, which is transmitted to the robotic system and controls the robot's actions. Therefore, it has very considerable application prospects in the field of human-computer interaction and human motion signal detection. PAM / CMC / DA / MXene hydrogel pressure sensors have excellent mechanical properties, electrical properties, adhesion properties, etc., and provide more reliable solutions for flexible wearable electronic skin, human-computer interaction, tactile perception and other fields.
[0085] The above description of the disclosed embodiments enables one skilled in the art to implement or use the present invention. Various modifications to these embodiments will be apparent to one skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention will not be limited to the embodiments shown herein, but rather to the widest scope consistent with the principles and novel features disclosed herein.
Claims
1. A MXene-based flexible hydrogel, characterized in that: The MXene-based flexible hydrogel is a PAM / CMC / DA / MXene hydrogel, which is a composite hydrogel prepared by a one-pot polymerization method using acrylamide AM, sodium carboxymethyl cellulose CMC, dopamine DA, and MXene; wherein MXene is obtained by etching titanium aluminum carbide powder with a lithium fluoride hydrochloric acid solution.
2. A method for preparing a MXene-based flexible hydrogel as claimed in claim 1, characterized in that: The method specifically comprises the following steps: 1) First, Ti3AlC2 is selectively etched with hydrochloric acid / lithium fluoride etching solution to obtain MXene nanosheets, and then a dispersed MXene solution is obtained by ultrasound and centrifugation; 2) After fully stirring AM, CMC, DA and the MXene solution prepared in step 1), N,N'-methylenebisacrylamide (MBAA) and 2,2'-azo[2-(2-imidazoline-2-yl)propane] dihydrochloride (AIBI) were added for free radical polymerization, and the mixture was obtained by ultrasonication after stirring for 30 minutes for later use; 3) placing the solution prepared in step 2) in a vacuum environment to remove gas, and quickly pouring the treated solution into a silicone mold; under argon protection, in-situ polymerizing the mixed solution obtained in step 2) in a water bath to obtain a PCDM hydrogel, i.e., the MXene-based flexible hydrogel.
3. The method for preparing a MXene-based flexible hydrogel according to claim 2, characterized in that: In step 1), the operation of selectively etching Ti3AlC2 with hydrochloric acid / lithium fluoride etching solution to obtain MXene nanosheets is as follows: Ti3AlC2 was added in batches to a pre-cooled LiF / HCl solution and stirred for reaction. The solution was then washed and centrifuged until the pH value of the supernatant stabilized at 6. The resulting precipitate was dispersed in deionized water and sonicated under argon protection. The supernatant was centrifuged, separated, and collected to obtain a high-purity MXene nanosheet solution.
4. The method for preparing a MXene-based flexible hydrogel according to claim 3, characterized in that: In the LiF / HCl solution, the mass ratio of lithium fluoride to hydrochloric acid is 1: (4.8-5.2); the mass ratio of the LiF / HCl solution to Ti3AlC2 is (5.2-5.5): 1, and the temperature of the entire reaction mixture is maintained at 40°C-50°C, and continuous stirring is ensured within this temperature range for 24 hours.
5. The method for preparing a MXene-based flexible hydrogel according to claim 2, characterized in that: In step (2), the mass ratio of AM, CMC, DA and MXene solution is (10-40):1:1:(90-110); the mass ratio of acrylamide (AM) to N,N'-methylenebisacrylamide (MBAA) is (350-450):1, and the mass ratio of acrylamide (AM) to 2,2'-azo[2-(2-imidazoline-2-yl)propane] dihydrochloride (AIBI) is (60-70):1; the free radical polymerization temperature is 55-65°C, and the free radical polymerization time is 30 min.
6. The method for preparing a MXene-based flexible hydrogel according to claim 2, characterized in that: In step (3), the exhaust time is 2-3 hours, the in-situ polymerization temperature is 55-65°C, and the in-situ polymerization time is 3-4 hours.
7. Use of the MXene-based flexible hydrogel as claimed in claim 1 or the MXene-based flexible hydrogel prepared by the method as claimed in claim 2 in a pressure sensor.
8. The use according to claim 7, characterized in that: The MXene-based flexible hydrogel can be used in a hydrogel pressure sensor for human motion detection.
9. The use according to claim 7, characterized in that: The MXene-based flexible hydrogel can be used in robotic systems that control the robot's movements through pressure-induced electrical signals.
Citation Information
Patent Citations
Degradable, self-repairing and self-adhering conductive hydrogel and preparation method thereof
CN112011067A
Polyacrylamide-polyvinyl alcohol-MXene-PEDOT: PSS composite conductive organic hydrogel and application thereof
CN118063801A